2016
DOI: 10.3109/15376516.2016.1160963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of e-cigarette refill liquid with or without nicotine on liver function in adult rats

Abstract: This study was conducted to evaluate the effects of e-cigarette refill liquid administration alone or with nicotine on the antioxidant defense status, functional and histopathological changes in adult rat liver tissue. For this purpose, 32 rats were treated for 28 days as follows: control group was injected intra-peritoneally with physiological saline; e-cigarette 0% treated group received an intra-peritoneal injection of e-liquid without nicotine diluted in physiological saline, e-cigarette-treated group rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 31 publications
2
36
1
1
Order By: Relevance
“…In the current study, glycogen content and hepatic protein levels were found to significantly decrease after e-liquid or nicotine exposure [21]. In this study we did not find histopathological abnormalities in the tissues or organs of the mice exposed to 14 days EC with the vanilla-flavored E-liquid, suggesting non-toxicity at the dose used.…”
Section: Discussioncontrasting
confidence: 48%
“…In the current study, glycogen content and hepatic protein levels were found to significantly decrease after e-liquid or nicotine exposure [21]. In this study we did not find histopathological abnormalities in the tissues or organs of the mice exposed to 14 days EC with the vanilla-flavored E-liquid, suggesting non-toxicity at the dose used.…”
Section: Discussioncontrasting
confidence: 48%
“…There are as yet relatively few studies of the effects of ENDS in rodent models, however recent studies showed e-cigarette based vapor inhalation of nicotine in mice reduced body temperature and locomotor activity (Lefever et al 2017) and increased platelet activity (Qasim et al 2018), which together demonstrate the feasibility of the approach. The paucity of models is underlined by the fact that several recent studies have resorted to parenteral injection of e-cigarette refill liquids to determine effects in rats (Bunney et al 2018;El Golli et al 2016;Golli et al 2016;Harris et al 2015;LeSage et al 2016). Inhalation administration of nicotine is possible, since one study showed that inhalation of air bubbled through an aqueous solution of nicotine produces nicotine dependence and facilitates the acquisition of subsequent nicotine intravenous self-administration (Gilpin et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine is known to increase ROS by breaking down the mitochondrial respiratory chain (20) and to modify the antioxidant system (5,30). Moreover, we have previously shown that e-liquid treatment could induce a modification of oxidative status in different organs (10,11), especially in the testis causing steroidogenesis alterations (12). Thus, nicotine action could explain the obtained results of E-liquid group.…”
Section: Discussionmentioning
confidence: 78%
“…It was recently shown that e-cigarette liquid (e-liquid) aerosols exhibit oxidant reactivity by generating ROS, acting like nicotine (26,37). We have previously assessed the impact of e-cigarette refill liquid per se on rat liver (10), kidneys (11) and testis (12) using intraperitoneal (i.p.) injection.…”
Section: Introductionmentioning
confidence: 99%